Determination of HPLC Chromatogram Profile of Katuk (Breynia androgyna (L.) Chakrab. & N.P.Balakr) Plants from Ristoja's Results using Chemometric Analysis - Yunarto, Nanang; Alegantina, Sukmayati; Isnawati, Ani (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
The katuk plant was known as Sauropus androgynous (L.) Merr, but the name is changed to Breynia androgyna (L.) Chakrab. & N.P. Balakr since the publication of Chakrab's & N.P. Balakr in the 2012 Journal of Plant Taxonomists. The content of chemical compounds and secondary metabolites of katuk leaf are strongly influenced by different habitat or location. Therefore, the Center for Research and Development of Medicinal Plants and Traditional Medicines, National Institute of Health Research and Development (NIHRD) has conducted Research on medicinal plants and herbs (RISTOJA) results on 58 samples of katuk plants originating from 7 provinces and used by 13 ethnic groups in Indonesia. This study aims to obtain plant quality based on the description of the High-Performance Liquid Chromatography (HPLC) chromatogram profile, in order to obtain the suitability of the efficacy of medicinal plants with their benefits for the community in an area. Test using HPLC with a gradient mobile phase, mixture of acetonitrile and methanol for 60 minutes. The results of the chromatogram were analyzed chemometrically by using Principal Component Analysis (PCA) data interpretation. PCA results showed that from HPLC chromatograms at 254 nm and 366 nm, each gave 3 different clusters, namely Clusters A, B and C where each cluster has the same chromatogram profile of katuk plants. Cluster A which was identified at a wavelength of 254 nm was the most used cluster by 7 ethnic groups with a total of 28 Katuk samples. Similarly, the chromatogram at a wavelength of 366 nm with the largest cluster is cluster A which is used by 11 ethnic groups with a total of 45 samples of katuk plants. where each cluster had the same chromatogram profile of katuk Plants.